Controlled in situ preparation of A beta(1-42) oligomers from the isopeptide "iso-A beta(1-42)", physicochemical and biological characterization - Bozsó Zsolt (PEPTIDES, 2010)
beta-Amyloid (A beta) peptides play a crucial role in the pathology of the neurodegeneration in Alzheimer's disease (AD). Biological experiments (both in vitro and animal model studies of AD) require synthetic A beta peptides of standard quality, aggregation grade, neurotoxicity and water solubility. The synthesis of A beta peptides has been difficult, owing to their hydrophobic character, poor solubility and high tendency for aggregation. Recently an isopeptide precursor (iso-A beta(1-42)) was synthesized by Fmoc-chemistry and transformed at neutral pH to A beta(1-42) by O -> N acyl migration in a short period of time. We prepared the same precursor peptide using Boc-chemistry and studied the transformation to A beta(1-42) by acyl migration. The peptide conformation and aggregation processes were studied by several methods (circular dichroism, atomic force and transmission electron microscopy, dynamic light scattering). The biological activity of the synthetic A beta(1-42) was measured by ex vivo (long-term potentiation studies in rat hippocampal slices) and in vivo experiments (spatial learning of rats). It was proven that O -> N acyl migration of the precursor isopeptide results in a water soluble oligomeric mixture of neurotoxic A beta(1-42). These oligomers; are formed in situ just before the biological experiments and their aggregation grade could be standardized. (C) 2009 Elsevier Inc. All rights reserved.